Empirical Model of Bearing Temperature Saturation at Asahan II Hydro-Turbine-Generator - Gautama, Bagus Brahmantya (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2018)
Bearing temperature saturation is a common phenomenon observed during no-load run and full-load tests of Asahan II hydro-turbine-generators. Despite complex heat transfer mechanism involved behind it, simple model can be constructed to predict bearing temperature change with time. Confidence on the general form of such model is rather high because it is validated using abundant data collected during the past 35 years. Further investigations are also made to compare temperature saturations at different load, rotational speed, and performance of cooling coil.